Early apoptosis of porcine alveolar macrophages limits avian influenza virus replication and proinflammatory dysregulation - Chang, Pengxiang; Kuchipudi, Suresh V.; Mellits, K.H.; Sebastian, Sujith; James, Joe; Liu, Jinhua; Shelton, Holly; Chang, Kin-Chow (Nature Publishing Group, 2015)
Pigs are evidently more resistant to avian than swine influenza A viruses, mediated in part through frontline epithelial cells and alveolar macrophages (AM). Although porcine AM (PAM) are crucial in influenza virus control, their mode of control is unclear. To gain insight into the possible role of PAM in the mediation of avian influenza virus resistance, we compared the host effects and replication of two avian (H2N3 and H6N1) and three mammalian (swine H1N1, human H1N1 and pandemic H1N1) influenza viruses in PAM. We found that PAM were readily susceptible to initial infection with all five avian and mammalian influenza viruses but only avian viruses caused early and extensive apoptosis (by 6 h of infection) resulting in reduced virus progeny and moderated pro- inflammation. Full length viral PB1-F2 present only in avian influenza viruses is a virulence factor that targets AM for mitochondrial associated apoptotic cell death. With the use of reverse genetics on an avian H5N1 virus, we found that full length PB1-F2 contributed to increased apoptosis and pro-inflammation but not to reduced virus replication. Taken together, we propose that early apoptosis of PAM limits the spread of avian influenza viruses and that PB1-F2 could play a contributory role in the process.